The Effect of Nanoparticle Structure on the Thermodynamics and Kinetics of Proton-Coupled Electron Transfer Reactions to V2O5 - Osman Bunjaku; Mustafa Turan; Hannes V. Beyertt; Wael Barakat; Michael Dyballa; Bertold Rasche; Deven P. Estes (Journal of the American Chemical Society, 2026)
Abstract Proton-coupled electron transfers (PCETs) to metal oxides are key reactions for sustainable catalytic and energy storage processes. The factors that control PCET reactions on metal oxides are, however, not well understood, with the effect of particle morphology/surface faceting on the thermodynamics and kinetics of PCET being essentially untested. We measured the thermodynamics and kinetics of PCET from CpCr(CO)3H to five V2O5 samples of varying morphologies/surface faceting. Their nanostructures were assessed by Rietveld refinement accounting for preferred crystallite orientation, giving a semiquantitative measurement of surface faceting. PCET to V2O5 occurs via proton insertion-coupled electron transfer (PICET), where H· diffuses into the bulk of the particle. The thermodynamics of PICET are controlled by particle structure, with nonequilibrium morphologies requiring structural rearrangement during PICET. The kinetics of PICET are controlled by the rate of H· diffusion into the bulk, with diffusion along the interconnected V2O5 layers being 10x faster than between the layers. Samples with hindered H· diffusion also show low activity in the oxidation of methanol, demonstrating that diffusion of H· into the bulk occurs during catalysis. This work demonstrates that particle morphology is critical for PCET reactions to anisotropic metal oxides and must be considered when examining their reactivity.